Experimental Investigation of the Water Droplet Evaporation on Inclined Surfaces by Taguchi and ANOVA Optimization Analysis - Yildirim, Atalay; Agra, Ozden; Sevindir, Mustafa Kemal (ASME, 2024)
We experimentally investigated the evaporation characteristics of a sessile water droplet on a glass substrate with different surface roughness levels. The influence of five parameters is evaluated for the evaporation process: substrate temperature (30 degrees C, 45 degrees C, and 60 degrees C), surface roughness (P0, P600, and P60), droplet volume (3, 5, and 8 mu L), water droplets initial temperature (30 degrees C, 40 degrees C, and 60 degrees C), and inclination angle (0 deg, 45 deg, and 75 deg) of the glass substrate. The Taguchi orthogonal array design of L27 is utilized to establish minimal candidate trial points for experimental works, and more trials have been conducted to quantify the effects accurately. Then, analysis of variance (ANOVA) has been used to evaluate the evaporation times for the sessile droplets. The results indicate that evaporation times decrease with rising substrate temperatures, increasing substrate inclination angle, and increasing initial water droplet temperatures. In contrast, evaporation times rise with increasing surface roughness and droplet volumes. After evaluation of the ANOVA analysis, surface roughness levels and droplet volumes are considered the most influential parameters after substrate temperatures, which is the most effective parameter on the evaporation times. On the other hand, initial water droplet temperatures and substrate inclination angle are less effective considering droplet evaporation times. A linear regression fit was derived via ANOVA analysis for the evaporation time, and the best mean deviation was found to be 10% from the experiments. The experimental outcomes were compared to previous research, and correlations were derived. The proposed correlation has given good results considering experimental and literature data.
Keywords: sessile droplet; evaporation; inclined substrate; DOE; ANOVA; experimental techniques; experimental/measurement techniques; heat and mass transfer; natural and mixed convection; two-phase flow and heat transfer; HYDROPHOBIC HEATING SURFACE; LIQUID-DROPS; SESSILE DROPLETS; CONTACT ANGLES; CONVECTION; SUBSTRATE; DYNAMICS; PLANE; Thermodynamics; Engineering